Metahuman KAGURI 0.1 as The Learning Media Innovation for Local Arts and Culture Exploration - Aquita Valentina; Welly Suryandoko; Autar Abdillah (University of Muhammadiyah Malang, 2025)
This research aims to create a learning media utilising Metahuman technology, named